Angiomyxoma of the Breast: A Clinicopathologic Analysis of 40 Cases. (1st March 2023) - Baranov, Esther; Alston, Erin L.J.; Lester, Susan C.; Fletcher, Christopher D.M.; Doyle, Leona A.
Abstract : Superficial angiomyxoma is an uncommon benign mesenchymal neoplasm that usually arises in dermis/subcutis of the extremities or trunk. Some tumors are associated with Carney complex. When arising in breast, these tumors are not well-recognized, mainly due to a lack of uniform nomenclature in the literature. This study therefore aims to improve recognition of angiomyxomas of the breast region. Forty cases were identified: demographics, presence of Carney complex, imaging and histologic features, PRKAR1A expression, and outcomes were evaluated. There were 22 female and 18 male patients (median age 40 years, range: 14 to 72). Most tumors presented as slowly-growing masses (77%). All but one were solitary, and median size was 1.5 cm. Tumors were superficial (dermal/subcutaneous) in 52.5% and deep/parenchymal in 47.5%. Nine involved the nipple-areola complex. All showed characteristic features of superficial angiomyxoma: poorly circumscribed, hypocellular, myxoid neoplasms with lobulated (55%) or infiltrative (45%) architecture, bland spindled fibroblasts, prominent thin-walled vessels, and admixed neutrophils. Tumors involving the nipple-areola complex infiltrated through areolar smooth muscle, and deep/parenchymal tumors showed entrapment of lobules mimicking myxoid fibroadenoma. Mitoses were typically absent, as was significant atypia. Cystic change was common. Two-thirds showed loss of PRKAR1A expression by immunohistochemistry. Two patients had Carney complex (7%). Recurrence after incomplete excision occurred in 1 patient. Angiomyxoma of breast may arise at superficial, nipple-areola or deep/parenchymal locations, where it can be difficult to recognize classic histologic features. Loss of expression of PRKAR1A is not invariable, but may be a helpful diagnostic clue. Recognizing angiomyxoma is important for 2 reasons: first, the recurrence rate is low and therefore wide excision is not essential, and second, it may allow detection of Carney complex in some patients.